2021
DOI: 10.1016/j.yebeh.2020.107559
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of the medial orbitofrontal cortex in humans elicits pleasant olfactory perceptions

Abstract: Background: Olfactory hallucinations can be part of epileptic seizures of orbitofrontal origin. Olfactory hallucinations, however, are rare and therefore the semiology, localization and lateralization characteristics are underdetermined. In addition, many discrepancies are found in the literature regarding olfactory processing and orbitofrontal (OF) functions and olfactory function. Particularly, the questions of laterality and affective component in coding of odors in the OF cortex remain controversial. Aims:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…However, a recent study on human participants demonstrated that, akin to rodents, pleasant but not negative odors are preferentially processed in the olfactory tubercle ( 59 ). Moreover, intracranial electric stimulation of the OFC, an area previously linked to odor valence processing in humans, could only produce pleasant odor experiences ( 60 ). This separation between valence extremes support the 2D valence hypothesis postulating that odor valence perception is not represented by a unidimensional spectrum, ranging from unpleasant to pleasant.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study on human participants demonstrated that, akin to rodents, pleasant but not negative odors are preferentially processed in the olfactory tubercle ( 59 ). Moreover, intracranial electric stimulation of the OFC, an area previously linked to odor valence processing in humans, could only produce pleasant odor experiences ( 60 ). This separation between valence extremes support the 2D valence hypothesis postulating that odor valence perception is not represented by a unidimensional spectrum, ranging from unpleasant to pleasant.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this regional-specific valence separation in processing also occurs in humans is not known. However, a recent study demonstrated that intracranial electric stimulation of the OFC, an area previously linked to odor valence processing in humans, could only produce pleasant odor experiences (Bérard et al 2020). The separation demonstrated in rodents does, however, support the 2-dimensional valence hypothesis that odor valence perception is not represented by a unidimensional spectrum, ranging from unpleasant to pleasant.…”
Section: Discussionmentioning
confidence: 89%
“…To ensure the quality of skull dissection and the accuracy of gray matter/white matter boundary segmentation, the results of skull dissection and brain tissue segmentation were examined by two skilled anatomical operators. After the cortical reconstruction was completed, the left and right hemispheres were divided into 33 brain regions according to the FreeSurfer cortical atlas ( 15 ), and the average CT and the summed SA of each brain region were calculated. Linear mixed effect (LME) ( 16 ) models were used to model the development trajectory, and three models (linear, quadratic, and logistic curve) were used to fit the trajectory.…”
Section: Methodsmentioning
confidence: 99%